Navigating Dual-Structured Crisis: Factors Influencing Nonprofit Organizational Resilience - Vien, Ha B.; Hoang, Thanh Thi (Nonprofit and Voluntary Sector Quarterly, 2026)
The COVID-19 pandemic constituted an unprecedented exogenous shock to many nonprofit organizations, testing their ability to sustain operations and adapt to crises. Building on population ecology and nonprofit organizational resilience framework, this study conceptualizes COVID-19 as a dual-structured crisis and examines how organizational factors, coupled with resilience tactics, shape nonprofit resilience. Results from 169 nonprofits highlight that specialist organizations (art and culture) are more vulnerable to external crisis than generalist nonprofits (human services). While donor support was critical for sustaining human-service organizations, peer support from other nonprofits emerged as a key factor for arts and culture organizations. In addition, system-wide constraints muted the effects of traditional strategies such as technology adoption and federal funding access on nonprofit resilience. Our findings underscore the context-dependent effectiveness of resilience tactics and offer new insights into managing nonprofits in future crises.
Keywords: dept.pch

Mandate for Leadership: The Conservative Promise By D.Bakst, J.Berry, L. M.Burke, D. R.Burton, A.Candeub, D. J.Carmack, B.Carr, B. S.Carson, P.Sr., Dans, K.Cuccinelli, R.Dearborn, V.deRugy, D.Devine, D.Furchtgott‐Roth, T. F.Gilman, M. M.Gunasekara, G.Hamilton, J.Hazelton, K.Kerrigan, D. D.Kirk, K.Lassman, B. L.McNamee, C.Miller, S.Moore, M.Namdar, P.Navarro, W. P.Pendley, M.Primorac, R.Severino, K. K.Skinner, B. D.Tucker, H. V.von Spakovsky, R.Vought, W. L.Walton, and P.Winfree, Washington DC: The Heritage Foundation. 2023. pp. ix‐887. ISBN: 978‐0‐89‐195174‐2 - Greenstein, Gabriel (Public Administration Review, 2025)
Keywords: Berry; Biology; Botany; Carr; Humanities; Philosophy; dept.psc

Exploring Perceived Fairness in Performance Evaluation Among Telecommuting Employees in Public Agencies - Aggarwal, Jyoti; Hoang, Thanh (Public Administration Quarterly, 2025)
Keywords: Business; Economics; Engineering; Marketing; Political science; Psychology; Public relations; Public sector; Telecommuting; Work (physics); dept.psc; fairness; federal government; organizational justice; performance evaluation; public sector; telecommute

Oral Hygiene Care of Older Adults and Caregiver Education: A Systematic Review - Asanza, Dachel; Njoku, Anuli; Baviskar, Snehal; Evans, Marian; Mouloudj, Kamel (Hygiene, 2025)
Background: There is a need to develop comprehensive guidelines to encourage the promotion of oral hygiene care among older adults and to assist caregivers in this endeavor, taking into consideration the specific challenges that arise from aging, comorbidities and caregiving. Methods: This review was conducted by searching across relevant literature from meta-databases including Academic Google, PubMed, Scielo and Scopus for studies published from 2020 to 2024. PRISMA guidelines were followed. We included articles that described oral hygiene methods, caregiver education and mechanization status of older adults. Common themes, best practices, and gaps in current guidelines were tracked using extracted and analyzed data. Results: The review revealed multiple factors affecting the oral hygiene of older adults, with themes relating to physical impairment, cognitive dysfunction, and caregiver involvement. Highlighted between the approaches are individualized therapy for oral hygiene, caregiver education, and the use of technology to improve adherence to oral hygiene. Barriers like dental care access, underlying medical conditions complicating dental treatments, and cost considerations were identified. Conclusions: The findings emphasize the necessity of clear recommendations that can help caregivers and advance dental care for older adults.
Keywords: Dental care; Hygiene; MEDLINE; Oral health; Oral health care; Oral hygiene; Promotion (chess); Scopus; aged; caregiver education; caregivers; dentistry; dept.pch; education; frail elderly; healthy aging; older adult; oral health; oral hygiene; oral medicine

Period Poverty Among Black, Hispanic and Low-Income Communities in the United States: Challenges and Recommendations - Njoku, Anuli; Alhassan, Mubarak; Tohura, Sharaban; Garcia, Kayla (Hygiene, 2025)
Period poverty refers to the lack of access to or affordability of menstrual hygiene supplies such as sanitary products and the inaccessibility of washing facilities, waste disposal and educational materials. Period poverty can significantly affect menstruating individuals’ physical, mental, and reproductive health and emotional wellbeing; negatively impact educational outcomes; cause financial strain; result in absenteeism from work and school; create barriers to healthcare access; and perpetuate poor health outcomes for generations. Barriers to menstrual equity include lack of access to period support, cost, poor sanitary facilities, lack of education, social and cultural stigma, and legal restrictions. Therefore, it is crucial to actively advocate for initiatives to increase access to menstrual hygiene products, raise public awareness, and educate individuals on safe menstrual practices. Approximately 500 million girls and women worldwide and an estimated 16.9 million people in the United States experience period poverty, with the issue being particularly common among marginalized groups such as Black or Hispanic menstruating individuals and those who are homeless, living in poverty, of low income, or attending college. This article investigates the physical, psychological, educational and social impacts of inequitable access to menstrual products, menstrual education, and sanitation facilities among menstruating individuals who are Black, Hispanic or of low income within the United States. We examine the threat this poses to health equity and propose recommendations to address this pervasive issue.
Keywords: Absenteeism; Equity (law); Health care; Hygiene; Poverty; Public health; Sanitation; Socioeconomic status; dept.pch; environmental sustainability; gender disparities; health equity; menstrual education; menstrual health; menstrual health management; menstrual hygiene products; period poverty; period tax; polycystic ovarian syndrome (PCOS); poverty alleviation; women’s health

Social justice with harm reduction approaches for mothers who use opioids: an international comparative ethnographic study with community engaged methods - Boeri, Miriam; Lamonica, Aukje; Whittaker, Anne; Bruce, Marisa (Harm Reduction Journal, 2025)
BACKGROUND: Mothers and pregnant women who use opioids are particularly vulnerable. Mothers often fear surveillance, stigma, and loss of custody of their children when seeking treatment. Although opioid agonist therapy (OAT) has been shown to be effective, access varies regionally, and not all mothers can cease using opioids. This study compares outcomes of mothers who use opioids in the UK with universal healthcare and OAT access, and mothers in the U.S. with restricted healthcare and OAT access, focusing on their interactions with services. METHODS: This is a secondary data analysis of two studies on mothers who use opioids. Data were collected from nine mothers in Scotland (UK) and 20 mothers in New Jersey (US) through ethnographic, longitudinal studies spanning one year. The UK study used a "Learning Alliance" engagement approach, a patient/public engagement model that involves stakeholders in developing objectives and the dissemination of findings. The US study engaged "community-based consultants," who are paid individuals with lived experience from the study field communities to assist researchers in recruitment and ethnographic fieldwork. Ethical approval was received from review boards. Data were anonymized before analysis, and people with lived experience provided feedback on findings. Grounded theory methods were used for analysis. RESULTS: Findings reveal both convergent and divergent experiences. Mothers in Scotland had more access to healthcare and social housing but faced increased surveillance, while New Jersey mothers often experienced housing insecurity and difficulty obtaining healthcare. Shared challenges included trust issues, stigmatization, inconsistent practitioner engagement, responsibilization, and unclear expectations from child protection services. While Scottish mothers had better access to OAT, both groups faced child custody loss due to unregulated drug use. Mothers in both studies were struggling to meet reunification requirements of abstinence (with or without OAT) within the required time frame. CONCLUSIONS: Differing governance structures create persistent challenges across national boundaries. While health practitioners generally support harm reduction strategies, it does not go beyond OAT for mothers. Our findings indicate the need for radical harm reduction approaches with social justice for mothers who use drugs, including safer parental drug use strategies.
Keywords: Child protection; Community engagement; Corporate governance; Criminal justice; Economic Justice; Ethnography; Harm; Harm reduction; Health psychology; Mothers who use drugs; Opioids; SAFER; Social policy; dept.pch

President Nixon and Senator Kennedy on Health Care: How Rivalry Shaped Reform - Hopper, Jennifer (Congress & the Presidency, 2025)
Keywords: Economics; Health care; Health care reform; Health policy; Law; Law and economics; Political science; Public administration; Rivalry; Sociology; dept.psc; peer-reviewed

One of these ads is not like the other: Viewer inability to differentiate issue ads from candidate ads - Forbus, R.; Marchant-Shapiro, T.; Singh, A.S. (International Journal of Interdisciplinary Civic and Political Studies, 2024)
For more than a decade, since the US Supreme Court ruled in Citizen’s United (2010), individuals and groups interested in the outcome of elections have increasingly donated to outside groups that avoid the restrictions imposed on candidates and traditional political action committees (PACs). As a result, total election spending more than doubled in the first five years and has continued to increase since then. Although American political advocacy groups refrain from formal electioneering, much of the increase in spending since Citizen’s United has been directed toward election campaigns under the guise of issue-advocacy ads. This raises the question of whether voters perceive a difference between candidate-sponsored ads and campaign-focused issue-advocacy ads. Unexamined is the impact that advertising by outside groups has on voters and whether voters are even aware of the sponsors of the ads they view. This study addresses whether voters can differentiate between ads sponsored by candidates or outside groups. Using an experimental design, we find that viewers cannot determine the sponsor of campaign ads, despite federal requirements for sponsor disclaimers. © 2024 Common Ground Research Networks. All rights reserved.
Keywords: Ad Differentiation; Ad Sponsorship; Campaign Ads; Issue-Advocacy Ads; Political Ad Disclaimers; Voter Perceptions; dept.mrk; dept.psc; peer-reviewed

Where are we when the community looks for us? A social network analysis of the self-organized network #TwitterFoodBank - Hoang, Thanh Thi (Communication and the Public, 2023)
Traditional crisis management approaches have often overlooked the role of community and nonprofit organizations. In this study, we investigated how nonprofits and communities contributed to problem-solving during crises through self-organization on social media. We applied social network analysis to 17,732 interactions using #TwitterFoodBank, a self-organized network emerged during the early stage of COVID-19 to address food insecurity. Our results highlighted the significant role of nonprofits in coordinating the community’s self-organized network. However, they also revealed a lack of coordination among these organizations in maintaining a viable network. These findings have valuable implications for nonprofits seeking to leverage the potential of online self-organized communities in crisis management.
Keywords: dept.psc; peer-reviewed

Small Power: How Local Parties Shape Elections by David Doherty, Conor M Dowling and Michael G Miller - Wharton, Jonathan L. (Political Science Quarterly, 2023)
Keywords: book.review; dept.psc

Staying Connected While Staying Distant: Social Media Engagement of Food Banks in Texas in the Wake of the COVID-19 Pandemic - Hoang, Thanh Thi (Human Service Organizations: Management, Leadership & Governance, 2023)
This study explores the social media engagement of human service nonprofits during the early phase of the COVID-19 pandemic. We analyzed 2,726 tweets from 15 food banks in Texas to understand their communication and audience engagement on social media. During the early outbreak, food banks were more active on social media, and these organizations primarily shared community-building and informational content. Before the pandemic, community-building content led to the highest engagement level. However, action and informational content saw greater engagement during the crisis. Our findings reveal that online audiences perceive the importance of each content type differently in varying circumstances. By understanding preferences and needs of online audiences, human service nonprofits can harness the power of social media to amplify their impact while operating during times of crisis.
Keywords: Audience engagement; crisis; dept.psc; food banks; peer-reviewed; social media

“Enquiring Minds Want to Know”: President Bill Clinton and the Blurring of News and Gossip - Hopper, Jennifer (A Gossip Politic: Rhetoric, Politics and Society, 2023)
This chapter explores the case of President Bill Clinton and the Lewinsky scandal as a pivotal moment in the convergence of political, technological, and cultural changes that elevated the presence of gossip and rumor in mainstream news sources, with major, lasting consequences. Throughout the unfolding of the scandal, unconfirmed and often salacious information about what had happened was transmitted among individuals and amplified through the media. The chapter takes a close look at some key elements contributing to such trends, including use of anonymous sourcing, heightened competition between media outlets, and the emergence of new media actors covering American politics and the presidency. An analysis of two specific incidents, involving coverage of allegations there were eyewitnesses to the president’s affair with Monica Lewinsky and that Lewinsky had a dress stained with the president’s DNA in her possession, demonstrates how prominent national news outlets publicized information reflecting weaker reporting standards and conveyed unsubstantiated rumors as news. As the news media devalued itself in cases such as this one, abandoning professional conventions and prioritizing sensational, entertaining content, the public began to no longer trust or rely on such sources to help it interpret events. We continue to see the ramifications of those developments in the present, with widespread belief in fake news, little consensus on what constitute facts or reality, and stark partisan divides about who can be relied upon to transmit the truth of political events. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: New media; President Bill Clinton; Scandal politics; The Lewinsky Scandal; dept.psc

Trade and the Environment - Buterbaugh, K. (Encyclopedia of Violence, Peace, & Conflict: Volume 1-4, Third Edition, 2022)
This article focuses on the complex interaction between trade and the environment. The first section reviews the debate among scholars on the environmental effects of trade. Next the article examines the role of the World Trade Organization and how its decisions have impacted the environment. This is followed by a discussion of climate change and its connection to trade. Finally, the article examines multilateral efforts to govern trade and control its environmental consequences as well as to encourage sustainable development. © 2022 Elsevier Inc. All rights reserved.
Keywords: Carbon leakage; Climate change; Comparative advantage; Environmental Kuznets curve; Externality; Free rider problem; Multilateral environmental agreements (MEAs); Nontariff barriers to trade; Pollution haven hypothesis; Prisoner's dilemma; The general agreement on tariffs and trade; World trade organization; dept.psc

Transit-Oriented Development (TOD) at a Political Crossroads - Wharton, Jonathan (The Earth & I, 2021)
Keywords: dept.psc; peer-reviewed

Pandemic Politics: Connecticut’s General Assembly and Gubernatorial Policymaking in 2020 - Wharton, Jonathan L. (New England Journal of Political Science, 2020)
Keywords: dept.psc; peer-reviewed; ⛔ No DOI found

Open Budgetary Meetings Amid a Pandemic: Assessing Connecticut's Various Pathways to Public Engagement During COVID-19 - Gil, Jodie M.; Wharton, Jonathan L. (The Journal of Civic Information, 2020)
Keywords: dept.jrn; dept.psc; peer-reviewed

Researching SCSU's Hilton C. Buley Library's New Haven Mayoral Archives - Wharton, Jonathan L.; Gil, Jodie (Connecticut History Review, 2021)
The mayoral archive includes both official and personal documents that can be used for research on various aspects of New Haven's history. Much of the DeStefano collection, for example, has various reports and studies on economic development and school construction projects, which were key to his administration.The Hilton C. Buley Library hosts a growing collection of mayoral papers from four New Haven mayors: Biagio “Ben” DiLieto (1980–90), John Daniels (1990–94), John DeStefano Jr. (1994–2014) and Toni Harp (2014–20). The materials are available to the public by appointment. Many items—including the full DeStefano papers—are available in a digital archive through the Buley Library website or the Connecticut Digital Archive portal. Jackie Toce, librarian and head of technical services at Buley Library, has spent the last seven years leading the digitization efforts for the archive, one of the reasons DeStefano donated the materials to Southern.4 Buley Library will host an exhibition and formal unveiling of the archive in late October 2021, which will run through the end of the year.
Keywords: dept.jrn; dept.psc; peer-reviewed